Implementing laparoscopy in Brazil´s National Public Health System: the bariatric surgeons´ point of view - SUSSENBACH,Samanta (2014)
BACKGROUND: Although Brazilian National Public Health System (BNPHS) has presented advances regarding the treatment for obesity in the last years, there is a repressed demand for bariatric surgeries in the country. Despite favorable evidences to laparoscopy, the BNPHS only performs this procedure via laparotomy. AIM: 1) Estimate whether bariatric surgeons would support the idea of incorporating laparoscopic surgery in the BNPHS; 2) If there would be an increase in the total number of surgeries performed; 3) As well as how BNPHS would redistribute both procedures. METHODS: A panel of bariatric surgeons was built. Two rounds to answer the structured Delphi questionnaire were performed. RESULTS: From the 45 bariatric surgeons recruited, 30 (66.7%) participated in the first round. For the second (the last) round, from the 30 surgeons who answered the first round, 22 (48.9%) answered the questionnaire. Considering the possibility that BNPHS incorporated laparoscopic surgery, 95% of surgeons were interested in performing it. Therefore, in case laparoscopic surgery was incorporated by the BNPHS there would be an average increase of 25% in the number of surgeries and they would be distributed as follows: 62.5% via laparoscopy and 37.5% via laparotomy. CONCLUSION: 1) There was a preference by laparoscopy; 2) would increase the number of operations compared to the current model in which only the laparotomy is available to users of the public system; and 3) the distribution in relation to the type of procedure would be 62.5% and 37.5% for laparoscopy laparotomy.